Neuroeconomics and reinforcement learning an exploratory analysis - Chavaglia, J.; Filipe, J. A.; Ferreira, M. A. M. (15th Conference on Applied Mathematics 2016, APLIMAT 2016, 2016)
In an era in which the study of the brain gets increasingly featured as an analytical tool of economic phenomena, the understanding of the way Neuroeconomics works as a tool for managers, students and other economic agents is now particularly important. There is now a need to have research that allow the clarification of the analytical decision process and the potential of brain study for decision making process of economic agents. Considering this new reality, a study is presented concerning one of the most important issues for the decision maker, which is the reinforcement learning process.